2011
DOI: 10.1007/s10329-011-0267-1
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of removal movements during social versus self-grooming among wild chimpanzees

Abstract: Grooming was observed in 11 wild chimpanzees (Pan troglodytes schweinfurthii) in Mahale, Tanzania, and the number of removal and stroke movements and grooming duration were recorded. Removal movements were more frequent during social grooming than during self-grooming. Chimpanzees used one or both hands for grooming, and grooming using both hands was more efficient for removing small objects. Due to physical constraints, self-grooming of the arms was almost always done using only one hand. The removal movement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 24 publications
0
3
1
Order By: Relevance
“…The present study underlines the importance of future studies to distinguish the network formed by the accumulation of play interactions from those formed by other types of affiliative interactions, such as grooming. While previous studies have shown that grooming decreases stress [Schino et al, ; Terry, ] and parasite numbers [Zamma, ], the current study reveals the importance of social play in the social development of chimpanzees. Even if they are all affiliative, behaviors such as social play, grooming, greeting, or embracing have specific social functions.…”
Section: Discussioncontrasting
confidence: 57%
“…The present study underlines the importance of future studies to distinguish the network formed by the accumulation of play interactions from those formed by other types of affiliative interactions, such as grooming. While previous studies have shown that grooming decreases stress [Schino et al, ; Terry, ] and parasite numbers [Zamma, ], the current study reveals the importance of social play in the social development of chimpanzees. Even if they are all affiliative, behaviors such as social play, grooming, greeting, or embracing have specific social functions.…”
Section: Discussioncontrasting
confidence: 57%
“…Our study shows that social play, rather than social grooming, might be a better first introduction for juveniles of primate species to experience social lives with individuals other than their own mothers or relatives. In addition, one of the important functions of social grooming is the hygienic function to remove ectoparasites from the bodies of other individuals (Zamma, ). Juvenile macaques must acquire the technique of grooming other individuals during development (Merrick, ; Nakamichi, ).…”
Section: Discussionmentioning
confidence: 99%
“…Focal animal sampling methods were used to collect data by MS (Altmann, ; Martin & Bateson, ). A digital video camera (SONY HDR‐SR8, Tokyo, Japan) or field notes were used to record social play (Hayaki, ; Shimada, ; Thierry, ), social grooming (Dunbar, ; Zamma, ), and other daily activities. On each observation day, MS selected, followed, and observed a single focal individual, so that the total observation time of each individual would be approximately equal.…”
Section: Methodsmentioning
confidence: 99%
“…Grooming is an important activity for group-living primates. It has hygienic ( Tanaka and Takefushi 1993 ; Zamma 2002 , 2011 ) and physiological functions such as stress reduction ( Schino et al. 1988 ; Keverne et al.…”
mentioning
confidence: 99%